2014
DOI: 10.2298/apt1445229r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Morus species in respect to micro, macro, and toxic elements

Abstract: This study examines the mineral composition of the extracts of the fruits, leaves and roots of white mulberry (Morus alba L.) and black mulberry (Morus nigra L.) grown in Serbia. All extract samples of white and black mulberry were analyzed for the content of micro (B, Co, Cr, Cu, Fe, Li, Mn, Ni, Se, Sr, Zn), macro (Ca, Mg, Na), and toxic metals (Al, As, Cd, Hg, Pb) by inductively coupled plasma optical emission spectrometry (ICP-OES). The study revealed that parts of the plant had statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The minerals content of WML-P is in Table 1D. Among minerals, Ca and Mg were present in the highest amounts and were similar to those found in Thai and Serbian WML [39,40]. Content of Fe and Mn, cofactors of many enzymes, including catalase in photosynthetic cells, did not change after conditioning.…”
Section: Chemical Compositionmentioning
confidence: 60%
“…The minerals content of WML-P is in Table 1D. Among minerals, Ca and Mg were present in the highest amounts and were similar to those found in Thai and Serbian WML [39,40]. Content of Fe and Mn, cofactors of many enzymes, including catalase in photosynthetic cells, did not change after conditioning.…”
Section: Chemical Compositionmentioning
confidence: 60%
“…This could be of great significance since this mineral plays a role in oxygen and electron transfer. Moreover, it is essential element for hemoglobin, myoglobin, cytochromes and some enzymes [46]. Table 5.…”
Section: Elemental Analysismentioning
confidence: 99%
“…Noordulin et al (2015) described that different mulberry genotypes and harvest time also influenced the calcium content. Other scientists have also confirmed the dependence of Ca levels on the characteristics of a cultivar (Radojković et al, 2014).…”
Section: Content Of Macroelements In White Mulberry Leavesmentioning
confidence: 79%
“…They discovered that the Mg content significantly increased with maturity. According to Radojković et al (2014), the first macroelement found in the extract of the M. alba and M. nigra leaves was Mg and the second was Ca. The increasing trend of Ca and Mg with the age of the leaf could be attributed to a limited mobility of these elements in the phloem (Leece, Gilmour, 1974).…”
Section: Content Of Macroelements In White Mulberry Leavesmentioning
confidence: 99%
See 1 more Smart Citation